Prinsip Individual Alfred Adler pada Tokoh dalam Novel Azzamine Karya Sophie Aulia: Kajian Psikologi Sastra - Risti Ariska; Dwi Widayati; Bambang Riyanto (Journal on Education, 2025)
This journal aims to discuss the Role of Government and Mass Media in the Socialization of Indonesian Business Law. In this study, we will conduct an analysis of the Actors of the MSME so that we can find out how much influence the Role of Government and Mass Media has in the Socialization of Indonesian Business Law. The type of research used is quantitative research using multivariate statistics and we conduct a Simple linear regression test to show how much the relationship between variables is. The research instrument is by distributing questionnaires to consumers. The results are to create statistics on the influence of the Role of Government and Mass Media in the Socialization of Indonesian Business Law, whether it has a significant impact on producers or vice versa. With this research, it is hoped that it can provide motivation for the Government to pay more attention to MSME actors and provide socialization to MSMEs to help their economy